Second harmonic generation in periodically poled MgO:LN crystal with 2 µm period created by e-beam irradiation. Issue 1 (19th May 2021) - Savelyev, E. D.; Akhmatkhanov, A. R.; Chezganov, D. S.; Vlasov, E. O.; Pashnina, E. A.; Shur, V. Ya.; Tronche, H.; Doutre, F.; Lunghi, T.; Baldi, P.
Abstract: The periodical domain structure with period 2 μm was created in 1-mm-thick MgO doped lithium niobate single crystals by electron-beam irradiation. The second harmonic generation (SHG) around 370 nm was obtained during pumping the crystals by 100 mW continuous wave tunable Ti:Sapphire laser. The normalized efficiency was 0.05%/W. The dependence of the SHG power on the pump beam position has indicated that the periodical domain structure depth is about 300 μm. The obtained results have demonstrated that the electron-beam poling can be used for creation of the short pitch periodical domain structures for light frequency conversion.